THE FEMININE LABEL, THE MASCULINE VOICE: BADDIECORE AND THE RACIALIZED GENDER CONSTRUCTION OF GENRE IN DIGITAL METAL COMMUNITIES - Belia, Athaya Prita; Meyrasyawati, Dewi; Arimbi, Diah Ariani (Rubikon : Journal of Transnational American Studies, 2025)
On 18 August 2023, “Baddiecore” emerged as a fan-coined label described as “metalcore with enough pop music crossover and sex appeal that normie hot people like it,” according to a viral X post by Craig Reynolds. Although bands like Sleep Token, Bad Omens, and Spiritbox were initially associated with the term, “Baddie” itself is rooted in Black American digital and feminist culture. This creates a tension when the genre is visually and sonically dominated by white male artists. This study examines how Baddiecore reflects the gendered construction of genre in digital metal communities, using the framework of postfeminist sensibility. Employing content analysis, the study draws 108 public posts on X between August 2023 and December 2024, using keywords like “Baddiecore” and associated band names. Findings show that Baddiecore was initially met with contestation due to its feminized tone but later gained acceptance, particularly among women fans engaging through merchandise and aesthetic participation. However, genre ownership remains centered around white male artists, with only two solo women and one female-fronted band visibly linked to the term. Ultimately, Baddiecore reveals how genre can operate as a site of aestheticized neoliberal femininity, shaped yet remains a space historically dominated by white, male voices.